SOURCES OF SOCIAL SUPPORT AND RESILIENCE AMONG ADOLESCENTS IN TANGERANG REGENCY - Puspitaningrum, Ni Putu Putri; Pudjiati, Sri Redatin Retno (Faculty of Psychology, Universitas Diponegoro, 2023)
Resilience is an important factor that can help a person to get through difficult phases in life. Current research focuses on dynamic resilience, which can be developed through interaction with the surrounding environment. In this study will be further analyzed the effect of each source of perceived social support on adolescent resilience in Tangerang Regency, as one of the areas prone to crime. Participants in this study were 429 junior high school students aged 13-16 years old. The study used The 14-Items Resilience Scale (RS-14) and The Multidimensional Scale of Perceived Social Support (MSPSS) which had previously been adapted by researchers. The results showed that perceived social support was a predictor of adolescent resilience in Tangerang Regency with a medium effect size, R2 = .166, F(1, 427) = 84.861, p = .000. In general, there is no difference between the social support received by male and female adolescents, t(427) = 0.402, p = .689. However, it was found that female adolescents feel more supported by friends compared to male adolescents, t(427) = -3.041, p = .003.